Computational Fluid Dynamics (CFD) Modelling & Simulation of 3D-Single Slope Basin Type Passive Solar Still to Improve Distillate Yield - Ansari, Shah Nawaz; Bhattarai, Nawraj; Neupane, Sanjaya; Bajracharya, Iswor (Advances in Engineering and Technology: An International Journal, 2025)
The Industrialization and population growth are causing a rapid surge in water demand. Earth has abundant water, but only 2.5% is fresh. Water pollution and industrial waste mixing with water make the freshwater impure. Therefore, the need for pure water is increasing. One of the solutions to this in rural areas could be using solar still as a distillation technique using solar energy. Despite the many advantages of being environment-friendly, simple, easily affordable, and abundant solar energy, low productivity is a major disadvantage of solar still. Merging with different types of auxiliary components, such as concentrators, phase change materials, collectors, etc., can increase output, but this will rise the cost of solar still. Thus, the primary challenge is to enhance the distillate yield i.e. productivity without significant increase in cost. Investigating and optimizing various performance parameters of solar still can improve the productivity of solar still. Hence, this paper performs the computational fluid dynamics (CFD) analysis to identify the parameters and their behaviors. FLUENT module in ANSYS is used for modelling and simulating the condensation and evaporation phenomenon of solar still to know the major parameters. Simulation for different water volumes in basin i.e. 20 litres, 15 litres and 10 litres was done. Result showed behavior of temperature and increment of 7% productivity while when volume was reduced from 20 litres to 10 litres. Based on the results, necessary conclusions and recommendations were given.